Principles and approach to developing mammalian cell culture media for high cell density perfusion process leveraging established fed‐batch media. (13th April 2017) - Lin, Henry; Leighty, Robert Woodrow; Godfrey, Scott; Wang, Samantha Boran
Abstract : Perfusion medium was successfully developed based on our fed‐batch platform basal and feed media. A systematic development approach was undertaken by first optimizing the ratios of fed‐batch basal and feed media followed by targeted removal of unnecessary and redundant components. With this reduction in components, the medium could then be further concentrated by 2× to increase medium depth. The medium osmolality was also optimized where we found ∼360 mOsm/kg was desirable resulting in a residual culture osmolality of ∼300 mOsm/kg for our cell lines. Further building on this, the amino acids Q, E, N, and D were rebalanced to reduce lactate and ammonium levels, and increase the cell‐specific productivity without compromising on cell viability while leaving viable cell density largely unaffected. Further modifications were also made by increasing certain important vitamin and lipid concentrations, while eliminating other unnecessary vitamins. Overall, an effective perfusion medium was developed with all components remaining in the formulation understood to be important and their concentrations increased to improve medium depth. The critical cell‐specific perfusion rate using this medium was then established for a cell line of interest to be 0.075 nL/cell‐day yielding 1.2 g/L‐day at steady state. This perfusion process was then successfully scaled up to a 100 L single‐use bioreactor with an ATF6 demonstrating similar performance as a 2 L bioreactor with an ATF2. Large volume handling challenges in our fed‐batch facility were overcome by developing a liquid medium version of the powder medium product contained in custom totes for plug‐and‐play use with the bioreactor. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:891–901, 2017